Contextual Requirements Elicitation through the Combination of Interviews, Scenarios and Visual Artifacts - Darin, Ticianne G. R.; Carneiro, Nayana; Paiva, Joseane O. V.; Santos, Ismayle S.; Andrade, Rossana M. C. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2020: Anais do XIX Simpósio Brasileiro de Qualidade de Software, 2020)
Population aging has demanded innovative software solutions to meet the elderly's needs, especially related to health. One of the challenges in this domain is developing solutions to favor the elderly's engagement. In general, they have a low educational level and lack basic health knowledge. The purpose of this article is to present an experience report on the use of contextual techniques and visual artifacts to improve the quality of the requirements elicited with caregivers for the elderly. This combination facilitated the collection of information with low literacy people and resulted in the refinement of previously identified requirements. The lessons learned here are expected to be useful for applications in this and other domains.